Oncolytic adenovirus Ad657 for systemic virotherapy against prostate cancer - Nguyen, Tien V (Oncolytic Virother, 2018)
BACKGROUND: Human species C adenovirus serotype 5 (Ad5) is the archetype oncolytic adenovirus and has been used in the vast majority of preclinical and clinical tests. While Ad5 can be robust, species C Ad6 has lower seroprevalence, side effects, and appears to be more potent as a systemic therapy against a number of tumors than Ad5. Historically, there have only been four species C human adenoviruses: serotypes 1, 2, 5, and 6. More recently a new species C adenovirus, Ad57, was identified. Ad57 is most similar to Ad6 with virtually all variation in their capsid proteins occurring in the hypervariable regions (HVRs) of their hexon proteins. Most adenovirus neutralizing antibodies target the HVRs on adenoviruses. This led us to replace the hexon HVRs in Ad6 with those from Ad57 to create a new virus called Ad657 and explore this novel species C platform’s utility as an oncolytic virus. METHODS: The HVR region from Ad57 was synthesized and used to replace the Ad6 HVR region by homologous recombination in bacteria generating a new viral platform that we call Ad657. Replication-competent Ad5, Ad6, and Ad657 were compared in vitro and in vivo for liver damage and oncolytic efficacy against prostate cancers after single intravenous treatment in mice. RESULTS: Ad5, Ad6, and Ad657 had similar in vitro oncolytic activity against human prostate cancer cells. Ad5 provoked the highest level of liver toxicity after intravenous injection and Ad657 caused the least damage in mice. Previous data demonstrated that Ad6 was superior to Ad5 at killing distant subcutaneous prostate cancer tumors in mouse models after a intravenous injection. Given this, Ad657 was compared to the Ad6 benchmark virus by single intravenous injection into mice bearing subcutaneous human DU145 prostate cancers. Under these conditions, Ad657 first infected the liver and then reached distant tumors. Both Ad6 and Ad657 mediated significant delays in tumor growth and extension of survival with Ad6 mediating higher efficacy. CONCLUSIONS: These data suggest that Ad657 may have utility as a local or systemic oncolytic virotherapy for prostate cancers. These data also lay the foundation for serotype-switching with oncolytic species C Ads.